From theoretical concepts to policies and applied programmes: the landscape of integration of oral health in primary care - Hermina Harnagea; Lise Lamothe; Yves Couturier; Shahrokh Esfandiari; René Voyer; Anne Charbonneau; Elham Emami (BMC, 2018)
Abstract Background Despite its importance, the integration of oral health into primary care is still an emerging practice in the field of health care services. This scoping review aims to map the literature and provide a summary on the conceptual frameworks, policies and programs related to this concept. Methods Using the Levac et al. six-stage framework, we performed a systematic search of electronic databases, organizational websites and grey literature from 1978 to April 2016. All relevant original publications with a focus on the integration of oral health into primary care were retrieved. Content analyses were performed to synthesize the results. Results From a total of 1619 citations, 67 publications were included in the review. Two conceptual frameworks were identified. Policies regarding oral heath integration into primary care were mostly oriented toward common risk factors approach and care coordination processes. In general, oral health integrated care programs were designed in the public health sector and based on partnerships with various private and public health organizations, governmental bodies and academic institutions. These programmes used various strategies to empower oral health integrated care, including building interdisciplinary networks, training non-dental care providers, oral health champion modelling, enabling care linkages and care coordinated process, as well as the use of e-health technologies. The majority of studies on the programs outcomes were descriptive in nature without reporting long-term outcomes. Conclusions This scoping review provided a comprehensive overview on the concept of integration of oral health in primary care. The findings identified major gaps in reported programs outcomes mainly because of the lack of related research. However, the results could be considered as a first step in the development of health care policies that support collaborative practices and patient-centred care in the field of primary care sector.